Knowledge of diagnosis, treatment strategies, and opinions on periodontal treatment procedures among general dentists in an Indian urban population: A questionnaire survey - Priya Sathyamurthy; Ashvini Padhye; Himani Swatantrakumar Gupta (Wolters Kluwer Medknow Publications, 2018)
Aim: A greater proportion of general dentists are unaware of the basic periodontal treatment needs as evidenced by the documented rise in advanced periodontal diseases culminating in tooth loss. Furthermore, limited data exist regarding the demographic predictors of referral for the specialty of periodontics. Therefore, the aim of the survey was to explore and evaluate the knowledge of diagnosis, treatment strategies, and opinions of general dentists on periodontal treatment procedures. Methods: This was a pilot survey utilizing a self-administered close-ended questionnaire consisting of 18 questions undertaken for 100 general dentists with a Bachelor of Dental Surgery degree. The questions were divided under 3 domains assessing the diagnosing ability, the treatment planning skills, and the dentists' perception of periodontal treatment outcomes. Based on their experience, the survey population was divided under three groups; Group I (n = 17) with <5 years of experience, Group II (n = 42) with 5 to <10 years of experience, and Group III (n = 33) with ≥10 years of practice. Pearson's correlation coefficient test was used to identify any significant associations between the responses. Results: On an average, 64.7% of correct responses were noted. About 95.7% of general dentists agreed that they performed complete scaling for all patients. Nearly 85.9% felt that there were higher chances for the recurrence of periodontal diseases and opted to retreat it. Maximum erroneous responses were given by Group II. A weak positive correlation between diagnosis and treatment planning questions was found. Conclusion: The current knowledge on diagnosis and treatment planning among dentists' is still truncated, and hence, the overall perception of the general dentists toward periodontal treatment in India needs to be gauged so that the general dentists can call for introspection and betterment of their services.